PENYULUHAN PERTANIAN INDONESIA : ISU PRIVATISASI DAN IMPLIAKISNYA - Subejo Subejo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2002)
The organization, mandate, and practices of agricultural and rural extension systems are changing worldwide, and it is vital that each region keep pace with the latest developments. The challenges of introducing appropriate institutional measures must be accepted by each government in order to reform the national agricultural extension systems in response to the global changes, otherwise the extension systems will become obsolete.Diverse agricultural extension funding and delivery arrangements have been undertaken since the mid-1980s by governments worldwide in the name of